Langmuir-Blodgett monolayers holding a wound healing active compound and its effect in cell culture: A model for the study of surface mediated drug delivery systems - Fernandez, Luciana Andrea (2021)
Langmuir and Langmuir-Blodgett films holding a synthetic bioinspired wound healing active compound were used as drug-delivery platforms. Palmitic acid Langmuir monolayers were able to incorporate 2-methyltriclisine, a synthetic Triclisine derivative that showed wound healing activity. The layers proved to be stable and the nanocomposites were transferred to solid substrates. Normal human lung cells (Medical Research Council cell strain 5, MRC-5) were grown over the monomolecular Langmuir-Blodgett films that acted as a drug reservoir and delivery system. The proliferation and migration of the cells were clearly affected by the presence of 2-methyltriclisine in the amphiphilic layers. The methodology is proposed as a simple and reliable model for the study of the effects of bioactive compounds over cellular cultures.